As estátuas vivas de Fortaleza-CE: performance, mimese e gesto - Soares, Ângela Vieira (2015)
This research deals with the living statues of Fortaleza-Ce in two spaces of acting: Ferreira Square (Praça do Ferreira) and Beira-Mar Avenue. During the years of 2013 and 2014 the performers were observed, chosen and interviewed, having as the bases of the interviews the narratives of their lives/trajectories. This resource was used for the comprehension of the individuals and their opinions about the work they do and as guide/inspiration for the theoretical and analytical path to follow. Departing from the observations and interviews the theoretical analysis founds itself on mimesis, understanding it as the base of the work and knowledge of these performers whose living statues are the result of a process of collage/(re)creation of diverse influences and images coming from what circulates in their sociocultural environment, an imitation of the material statuary (dead) whose base is the performers’ own bodies (alive). Upon this essential pair of opposed terms (dead x alive) unfolds another fundamental one for the practice and its esthetical end: immobility x mobility. The game between these complementary opposed is in the performance of the living statue and in its silence communication with the audience (in the relation between both) guided in certain theatricality. The living statues also evoke a tension between the legitimate and their marginal place as regards the art and formal work, tension between other and also opposed terms that define the doing of these performers as a social gestus. Research developed with the Laboratory of Investigation in Body Communication and Art (Laboratório de Investigação em Corpo Comunicação e Arte) – LICCA-CNPq.